A sustentabilidade fiscal do Brasil e do México, no período entre 1997 e 2016 - Jarros, Márcio Berlt (Universidade do Vale do Rio dos Sinos, 2017)
This study aims to investigate the fiscal sustainability of Brazil and Mexico between 1997 and 2016. The data indicates that occurred an inflection regarding the conduct of the fiscal policy, close to the subprime crisis of 2008, which intensified a change in the government behavior by the gradual deterioration of primary outcomes. The research methodology applied the models of cointegration and multicointegration with structural breaks, to evaluate the budgetary sustainability of central governments. The results of the two models were similar and pointed to a sustainable fiscal management for Mexico, which presented greater flexibility in budgetary adjustments. It was also verified the multicointegration relationship among revenues, expenses and the stock of debt. The evaluation of Brazil's fiscal results did not find evidences to prove the balance between revenues and expenditures in the two models, while budgetary adjustments presented rigidity. However, there was an increase in the public sector net debt in both countries, with a gradual increase in central government participation in the total debt. In sum, the models recommended significant adjustments in Brazil's expenditures, while a potentially explosive debt behavior tends to be more likely for Brazil and less likely for Mexico.
Keywords: Sustentabilidade fiscal; Multicointegração; Cointegração; Brasil; México; Fiscal sustainability; Multicointegration; Cointegration; Brazil; Mexico; ACCNPQ::Ciências Sociais Aplicadas::Economia